Malaysian murders and mysteries a century of shocking cases that gripped the nation - Vengadesan, Martin; Sagayam, Andrew (Marshall Cavendish Editions, an imprint of Marshall Cavendish International, 2020)
Malaysian Murders and Mysteries brings together 42 of the nation's most well-known and notorious cases - and investigates over a century of crimes and murders that have gripped the attention of the entire nation and beyond. The cases go as far back as 1875, beginning with colonial-era intrigues that remain unresolved to this day, to the swift and sudden demise of a North Korean man at KLIA in 2017 and a mysterious epidemic that killed 15 villagers in a remote Kelantan outpost in 2019. Based on the authors' meticulous research and consultations with several of Malaysia's most eminent historians and criminal lawyers, crime reporters and police officers, this compilation breathes new life into some of the cases and sheds new light on the notorious events.